An efficient route to prepare suspended monolayer for feasible optical and electronic characterizations of two‐dimensional materials. Issue 2 (23rd December 2021) - Huang, Yuan; Wang, Yun‐Kun; Huang, Xin‐Yu; Zhang, Guan‐Hua; Han, Xu; Yang, Yang; Gao, Yunan; Meng, Lei; Wang, Yushu; Geng, Guang‐Zhou; Liu, Li‐Wei; Zhao, Lin; et al.
Abstract: Two‐dimensional (2D) materials are highly sensitive to substrates, interfaces, and the surrounding environments. Suspended 2D materials are free from substrate‐induced effects, thus an ideal approach to study their intrinsic properties. However, it is very challenging to prepare large‐area suspended 2D materials with high efficiency. Here we report a universal method, based on pretreatments of densely patterned hole array substrates with either oxygen‐plasma or gold film deposition, to prepare large‐area suspended mono‐ and few‐layer 2D materials. Multiple structural, optical, and electrical characterization tools were used to fully evaluate the improved performance of various suspended 2D layers. Some of these observations reported in this study are: (1) Observation of a new Raman low frequency mode for the suspended MoS2 ; (2) Significantly stronger photoluminescence (PL) and second harmonic generation (SHG) signals of suspended WSe2, which enables the study of new optical transition processes; (3) The low energy electron diffraction pattern on suspended MoS2 also exhibits much sharper spots than that on the supported area; and (4) The mobility of suspended graphene device approaches 300 000 cm 2 V −1 s −1, which is desirable to explore the intrinsic properties of graphene. This work provides an innovative and efficient route for fabricating suspended 2D materials, and we expect that it can be broadly used for studying intrinsic properties of 2D materials and in applications of hybrid active nanophotonic and electronic devices. Abstract : A new efficient method to fabricate high‐quality and large‐area suspended two‐dimensional (2D) materials is developed. The superior properties of suspended samples over supported ones are proved by Raman spectra, photoluminescence spectra, second harmonic generation, low energy electron microscopy as well as mobility characterization. This work could facilitate the studies of the intrinsic properties of 2D materials and the applications of active 2D nano devices.